FOCUS RESEARCH ON HALAL FOOD MARKETING - Fadli Agus Triansyah (IAIN Surakarta, 2023)
Halal food is a category of food or beverage that Muslims may consume according to Islamic law. Halal cuisine must also adhere to strict standards of sanitation and hygiene, which makes it noted for its cleanliness and higher quality. This study utilised a systematic review on halal food marketing scopus database from 2021-2023. In this research, the keyword used is